Some Clarifications on the Transversality Condition - Michel, Philippe (Econometrica, 1990)
In this paper, the authors study a general concave discrete-time, infinite-horizon, optimal-control problem. They establish necessary and sufficient conditions for optimality in the weak sense of W. A. Brock and for optimality in the strong sense of D. Gale. The corresponding transversality conditions are general exhaustion properties of the limit value of the optimal state variables; these properties cover and extend the well-known results obtained in special cases. Copyright 1990 by The Econometric Society.